Hyponatremia in hospitalized patients with chronic kidney disease; aetiology, treatment, and outcome, in a tertiary care hospital, Dubai, UAE - Alalawi, Fakhriya; Seddik, Ayman Aly; Yousif, Hussain; Railey, Mohammad; Alhadari, Amna (International Journal of Research in Medical Sciences, 2021)
Background: Hyponatremia is common among hospitalized patients. Unfortunately, articles describing the management of profound hyponatremia (serum sodium <125 mEq/l) in the background of kidney disease are scarce. This review focuses on the incidence, prevalence, patient characteristics, and clinical features among hospitalized chronic kidney disease (CKD) patients with particular attention to CKD stage 3 to 5. Methods: 71 adult patients with CKD stage 3 to 5 and had presented with profound hyponatremia (serum sodium <125 mEq/l) were included. Patient demographic data, laboratory parameters and treatment received were recorded. The primary endpoint was the development of central nervous syste (CNS) manifestations, while the secondary outcomes included early mortality (death within 30 days). Results: 97 episodes of hyponatremia were recorded in 71 patients. 35 patients (49%) were UAE national and 53.5% patients were females. 52% were in CKD stage-5 refusing dialysis. Diabetic nephropathy was the underlying cause in 66%. The initial Sodium level upon admission ranged from 107-125 mEq/l, with a mean±standard deviation (SD) value of 117.7±4.54 mEq/l. The correction of hyponatremia had ranged between 24 hours in 60% of the patients to 96 hours. Diuretics were used in conjunction with the saline in 85%. Hospital stay ranged between 2-58 days (average 11.7 days). No CNS symptoms were recorded in any of the treated patients. Three patients had died (within 30 days) of sepsis of different sources. Conclusions: Management of hyponatremia in CKD patients remains challenging and should be directed to the underlying cause. Yet, complex patients with advanced CKD particularly in concurrence with heart failure might represent a medical dilemma. Administering hypertonic saline in different mixed concentrations depending on the volume status of the patients appear to be safe, efficient, and suitable for high-risk CKD patients while monitoring Sodium level carefully.